Discursive tensions between training and employment at the Doctorate in Social Sciences of the Autonomous University of Nayarit (Revista Electrónica Calidad en la Educación Superior, 2020)
Starting from the categories of discourse and significant, through an interpretative analysis of different bibliographic documentary sources and interviews with methodological resources of qualitative research, this paper puts in review discursive, institutional and subjective positions on the relationship between Academic training and job expectations in PhD students in social sciences of the Autonomous University of Nayarit and the areas of work occupation promoted in graduate profiles of graduate programs and policies for higher education in Mexico. Results that identify various relationships between thesis work, quality discourse and those projections that students elaborate on the possible work scenarios at the graduation stage are presented, entering into tension with institutional and global discourses.
Keywords: Education and employment; Postgraduate student; Discourse; Social Sciences